Interactive Media Development using Deep Learning-Based Smart Apps Creator to Improve Student Learning Outcomes in Science Learning in Grade V of SDN Nan Sabaris - Asmelawati Asmelawati; Ismira Ismira; Hafiz Hidayat (Journal of Educational Sciences, 2026)
This research was conducted based on the limited use of interactive learning media that can support the Deep Learning approach and improve elementary school students' science learning outcomes. The research aims to develop interactive media based on Smart Apps Creator and test its validity, practicality, and effectiveness. The strength of this research lies in the integration of the Deep Learning approach in media designed to increase students' active involvement, critical thinking skills, and contextual learning experiences. The method used is Research and Development with the ADDIE model which includes analysis, design, development, implementation, and evaluation. The research subjects were fifth-grade students at SDN 15 Nan Sabaris, SDN 17 Nan Sabaris, and SDN 16 Nan Sabaris. The results showed that the media was very valid with a validity score of 94.44% from material experts, 100% from language experts, and 93.18% from media experts. Teacher practicality scored 96.42%, 100%, and 92.85%, while student responses were 92.6%, 91.88%, and 91.87%. The effectiveness of the media shows N-Gain values of 0.81, 0.79, and 0.81 with a high category.